Legal Comparison of Standard Clause Regulations in Indonesian and New Zealand Consumer Protection Laws - Fauza, Farah (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
This study aims to identify and analyze the comparison of Standard Clauses regulations in Indonesian and New Zealand consumer protection laws. This research is normative legal research, in which this research obtains data from primary legal materials, including legal principles and legal norms contained in laws and regulations within the consumer protection sector in Indonesia and New Zealand, supported by secondary legal materials in the form of books, journals, articles, papers, previous research related to research problems. The results of this study indicate that there are notable differences between the regulations for the use of Standard Clauses in Indonesian and New Zealand consumer protection laws. These differences are observed in several aspects, such as the terminology used, the determination process for prohibited Standard Clauses, the legal implication of the use of Standard Clauses, and the legal accountability for business actors who include Standard Clauses prohibited by the law. Indonesia uses the term